RESEARCH ON SURVEY AND ASSESSMENT OF THE CONDITIONS AFFECTING ARSENIC ADSORPTION AND REMOVAL BY STEEL SLAG IN WATER - Trang, Tran Thi Thu; ChangMing, Yang; Shuo, Shen; Hiep, Le Minh (Vietnam Journal of Marine Science and Technology, 2015)
This paper presents the results of this research which utilizes solid waste resources in the environment, namely steel slag, to adsorp and remove arsenic in water. The study conducted empirical processes based on the processes in the experimental conditions affecting arsenic adsorption and removal by steel slag in contaminated water: concentration, steel slag size, steel slag weight, pollution concentration, temperature, symbiotic ions. The research results show: The lower initial solution concentration is, the more easily adsorption equilibrium can achieve, the higher initial concentration is, the longer it takes to reach adsorption equilibrium; the smaller steel slag particle is, the more easily adsorption equilibrium can reach; the larger particle size, the longer the time to reach adsorption equilibrium; the more increasing the number of steel slag particles, the greater the pollutant adsorption, the higher the removal efficiency; initial pH concentration affects As adsorption of steel slag (III); influence of temperature on As adsorption of steel slag (III) is not clear; different ions (NO3-, Cl‑, F-, SO42- and PO43-) intervene in As adsorption of steel slag (III) in solution. Thus, the choice of steel slag as the material to adsorb and remove arsenic in water is the optimal method, bringing economic efficiency, environmental protection and practical application.